Valuing value debate - Woods, Steven G. (Šolsko polje, 2007)
Given the increased polarization of societies, the need to be able to discuss the core values of those societies is a priority. In order for academic debateto serve as a training ground for discussion in the public sphere the ability to engage in discourse and discussion of values coherently and effectively is called for. The paper will provide a primer for effective valuedebate, focusing on identifying values, criteria construction, and dealing with the clash of competing values. Examples of topics will be explored, and a discussion of how the transition beyond academic debate to debating values in the public sphere can be achieved will also be presented.
Keywords: argumentacija; debata; kritično mišljenje; retorika; učenje; vrednote